Infra-structure Study of Information in Iraqi Universities and it’s Surroundings (Al-Mansour Journal, 2023)
Information production is one of the main economic sectors in the world and an indicator of power. Hence the first step toward building and utilizing the information is to identify and study the scope of existence its infrastructure and the factor that be able to employ them. In our paper we identify and evaluate the infrastructure of information in our universities.Then we point out the way to overcome the backwardness in the vital sector and emphases on the importance of information policy and its role to develop and utilize the existence of information infrastructure according to our societies needs.Also, we discuss the situation of related subject in the Arab World, and the absent of harmony and integrity between them. We have reached to some results such as:Although the existences of infrastructure but it dose not meet the social requirement without putting certain policy to utilize infrastructure, integrate and establish bridge of knowledge between Arab countries.